2022
DOI: 10.1007/s40520-022-02109-9
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary collaboration and computer-assisted home healthcare referral in the emergency department: a retrospective cohort study

Abstract: Aim Home healthcare (HHC) provides continuous care for disabled patients. However, HHC referral after the emergency department (ED) discharge remains unclear. Thus, this study aimed its clarification. Methods A computer-assisted HHC referral by interdisciplinary collaboration among emergency physicians, case managers, nurse practitioners, geriatricians, and HHC nurses was built in a tertiary medical center in Taiwan. Patients who had HHC referrals after ED discharge bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The second stage is known as home-based primary care plus, aims to provide additional skilled nursing care to homebound patients [7,10]. Nurse visits are added to physician visits in this stage [7,10]. The third stage is home-based palliative care, which aims to provide end-of-life care for patients diagnosed with serious illnesses [10].…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stage is known as home-based primary care plus, aims to provide additional skilled nursing care to homebound patients [7,10]. Nurse visits are added to physician visits in this stage [7,10]. The third stage is home-based palliative care, which aims to provide end-of-life care for patients diagnosed with serious illnesses [10].…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…This change aims to encourage physicians to provide care outside of hospitals, expand options for seeking medical assistance, and promote changes in patients' health-seeking behavior [6,7]. The HMIP model integrates health literacy, rehabilitation, home-based medical care, home-based nursing, community palliative care, and end-of-life care, while building community resources networks and providing high-quality community care services [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, the CMMC initiated HHC and has provided continuous and holistic care to its patients [12]. The HHC in CMMC includes not only the patients in need after hospital discharge but also those who are directly discharged from the ED [7]. We included all patients who received HHC between August 1, 2019, and July 31, 2021, in this study (Figure 1).…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…The aim of HHC is for aging in place as well as reducing ED visits and hospitalization [6]. ED visits during HHC are indicators of negative outcomes [2,7,8], which increases the burden on families and medical insurance. Previous studies reported that approximately 20-30% of patients who receive HHC may visit the ED or get hospitalized [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In response to these challenges, the Chi Mei Medical Center (CMMC) established a geriatric ED in 2019 to enhance the quality of care for older ED patients [8]. Various geriatric care protocols have been implemented and published, encompassing hospice and palliative care, geriatric syndrome screening, medication reconciliation, delirium screening, treatment, and referrals for home healthcare [9][10][11][12][13][14]. Within this context, we developed a novel computer-assisted model for TFU and conducted this study to elucidate its impact on the Asian population.…”
Section: Introductionmentioning
confidence: 99%